2017
DOI: 10.1016/j.jallcom.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characteristics of pre- and post-annealed sol-gel derived CoCu-oxide coatings

Abstract: Sol-gel derived CuCo-oxide coatings as solar selective surfaces, synthesized onto aluminium substrates at various annealing temperatures, are analysed by correlating their structural, chemical bonding states, and surface morphological topographies. As the annealing progressed, all the coatings displayed a Cu 0.56 Co 2.44 O 4 (ICSD 78-2175) phase with preferential orientation along (400) reflection plane. Rietveld refinement of X-ray diffraction (XRD) data indicate that residual stress and microstrains develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…These parameters are consistent with that obtained from our previous X-ray diffraction study: a ¼ 8.09Å. 27 In the current cluster model of Cu 0.5 Co 2.5 O 4 , there are 4 Cu, 20 Co and 32 O atoms. The crystal structure was optimized and is shown in Fig.…”
Section: Theoretical Predictionssupporting
confidence: 91%
See 3 more Smart Citations
“…These parameters are consistent with that obtained from our previous X-ray diffraction study: a ¼ 8.09Å. 27 In the current cluster model of Cu 0.5 Co 2.5 O 4 , there are 4 Cu, 20 Co and 32 O atoms. The crystal structure was optimized and is shown in Fig.…”
Section: Theoretical Predictionssupporting
confidence: 91%
“…First-principles calculation is one of the most promising approaches to predict the ground state properties of a material. The XRD results from Miran et al 27 revealed that the adopted phase for this coating material, as annealing temperature progress within the same range of temperatures is, Cu 0.56 Co 2.44 O 4 . The Cu 0.5 Co 2.5 O 4 system was dealt with the level of density functional theory (DFT+U) proposed by Dudarev et al 28 as implemented in the Cambridge Serial Total Energy Package (CASTEP) 29,30 of Material Studio.…”
Section: Density Functional Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…The three key parameters namely, the mean surface roughness, R a , rms value of surface roughness, R q , and z scale were estimated from the AFM micrographs. The mean surface roughness, R a of a thin film materials can be calculated using [50],…”
Section: Afm Imagingmentioning
confidence: 99%